Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Turnover Intention melalui Kepuasan Kerja - Rani Dwi Rahadiyanti; Wawan Prahiawan (Jurnal Syntax Admiration, 2024)
This study aims to examine the effect of work stress and work environment on turnover intention by considering job satisfaction as a mediating variable. This study used a quantitative type of research. The population in this study is employees of PT. Donghwa Electric Engineering consists of 183 direct man power and 27 indirect man power with a total population of 210 respondents as of September 2023. The result, that work stress and work environment have a negative but not significant effect on turnover intention at PT. Donghwa Electric Engineering, so the first (H1) and second (H2) hypotheses were rejected. However, work stress and work environment have a positive and significant effect on job satisfaction, so the third (H3) and fourth (H4) hypotheses are accepted. Job satisfaction has a positive and significant effect on decreasing the intention to leave work, supporting the fifth hypothesis (H5).